IMPLEMENTATION OF HEALTH SERVICES TO PRISONERS IN OVERCROWDED CONDITIONS AT CLASS IIA AMBARAWA PRISON - Widyardi, Aditya Rafif; Rachmayanthy, Rachmayanthy (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This article discusses the implementation of health services to prisoners in overcrowded conditions at Class IIA Ambarawa prison. Health services are implemented only by one nurse, not by a doctor. This is a problem because the conditions at Ambarawa Prison are overcrowded. In addition to health human resources issues, the available health facilities are also limited. This study aims to determine how the implementation of health services to prisoners is carried out in overcrowded conditions, and what obstacles are faced in its implementation. Through an in-depth understanding of this issue, this article is expected to improve the quality of health services from the writing made. This research uses a descriptive qualitative approach to understand the phenomenon by going directly to the field, so that it can be described in detail about the conditions that occur. Data collection was carried out by interviewing 8 resource persons, through the observation process, and documentation studies. While data processing is done with NVIVO 14, so that the data received can be more trusted in its validity. Keywords: Service Health; Overcrowded; Human Resource; Facilities